MANAGEMENT AND PREVENTION OF ABUSES IN SPORTS - COSTIN DAN EUGEN; POPESCU MARIUS CĂTĂLIN; PĂSĂRIN LEONARDO DANIEL; POPA MARIAN GABRIEL; DIACONESCU DRAGOȘ LAURENȚIU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2024)
Sport has always played an important role in society, bringing joy, excitement and a sense of community as well as national pride. Over the centuries, sport has evolved from simple local competitions to global events watched by millions of people, gaining ever greater socio-political and economic importance. In the paper "Management and prevention of abuses in sports" we make a brief presentation of the types of abuses existing in sports and the solutions that can be used to eliminate these harmful actions, including a survey conducted on this topic.